2014
DOI: 10.1007/s10735-014-9578-z
|View full text |Cite
|
Sign up to set email alerts
|

Age-related changes in the distribution of transient receptor potential vanilloid 4 channel (TRPV4) in the central nervous system of rats

Abstract: Transient receptor potential vanilloid type 4 (TRPV4) channels are expressed in the central nervous system, but their role in regulating the aging process under physiological and pathological conditions is still largely unknown. To identify age-related changes in the TRPV4 channel that contribute to the central nervous system, we investigated the distribution of TRPV4 in the brain and spinal cord regions of adult and aged rats. The expression of TRPV4 in the brain and spinal cord of adult and aged Sprague-Dawl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Although TRP channels have been reported to be involved in lifespan regulation in C. elegans (95), changes in worm TRPV activation with respect to aging have not been clarified yet. Studies mainly in mammalian systems have indicated that expression or distribution of TRPV channels is affected by aging (96,97). Our experiments show that age increases the magnitude of the "on" and the "off" responses ( Figure 3C, 3D Figure 4C, 4D.…”
Section: Ca 2+ Dynamics Reveal the Effect Of Age And Stress On Ca 2+ supporting
confidence: 51%
“…Although TRP channels have been reported to be involved in lifespan regulation in C. elegans (95), changes in worm TRPV activation with respect to aging have not been clarified yet. Studies mainly in mammalian systems have indicated that expression or distribution of TRPV channels is affected by aging (96,97). Our experiments show that age increases the magnitude of the "on" and the "off" responses ( Figure 3C, 3D Figure 4C, 4D.…”
Section: Ca 2+ Dynamics Reveal the Effect Of Age And Stress On Ca 2+ supporting
confidence: 51%
“…Furthermore, the neuronal calcium amplitude during PIDs was also attenuated in Trpv4–/– mice, suggesting that TRPV4 channels participate in at least three possibly related pathways during stroke—calcium influx into astrocytes, extracellular accumulation of glutamate, and calcium overload of neurons. Whether the calcium influx into neurons is caused by glutamate released from astrocytes, or is related to TRPV4 expression by neurons (Lee & Choe, ), or a combination of the two, remains to be shown. However, as all of these pathways have been shown to trigger neuronal death during ischemia (Rossi, Brady, & Mohr, ), our data suggest that TRPV4 inhibition may be a potential therapeutic target in future translational and possibly clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…First, TRPV4 expression is not widespread but limited to distinct brain regions, including the upper cortical layers where our imaging experiments were performed (Benfenati et al, ). As spontaneous PIDs typically begin in the infarct core, that is, the basal ganglia, where TRPV4 expression is low (Lee & Choe, ), it may be speculated that other pathways prevail in the generation of PID, although PIDs have been shown to emerge from other regions as well (von Bornstädt et al, ). Second, although iGluSnFR is an excellent tool to map the temporal dynamics of glutamate, it may fall short in faithfully reporting differences in the absolute concentration of glutamate, as iGluSnFR may saturate before peak glutamate levels during PIDs are reached (Fabricius, Jensen, & Lauritzen, ; Haustein et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TRPV4 channels were also reported to be highly expressed in human hippocampal neurons (http://www.proteinatlas.org/ENSG00000111199-TRPV4/tissue/hippocampus) (Kauer and Gibson, 2009) and involved in Aβ(40)-induced hippocampal cells death and astrocytic Ca 2+ signaling (Bai and Lipski, 2014). TRPV4 expression was also shown to be upregulated with age and injury in human (Bai and Lipski, 2014;Jie et al, 2016;Lee and Choe, 2014). Besides, as a calcium permeable channel, TRPV4 channel also contributes to the resting membrane potential (Shibasaki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%